Original paperAdenosine and neutrophil CD11b/CD62L and oxidative burst in stable ischemic heart disease - Rysz, Jacek; Błaszczak, Robert; Kędziora-Kornatowska, Kornelia; Kujawski, Krzysztof; Jabłoński, Sławomir; Markuszewski, Leszek (Archives of Medical Science, 2005)
Objectives: The immune response to endogenous as well exogenous stimuli is modified by various factors including drugs. Adenosine is an endogenous nucleotide involved in cellular energy metabolism. Adenosine receptors may influence the biological activity of numerous cells, regardless of sporadic or continuous manner of cellular adhesion under physiological conditions. These receptors are capable of specific recognition of cellular surface antigens, cellular segregation and the control of cellular morphology. Material and methods: We evaluated the effect of a single, intravenous dose of adenosine on the respiratory burst of polymorphonuclear leucocytes and the expression of their cell surface adhesion antigens CD11b and CD62L in 20 male patients with stable ischaemic heart disease. Expression of CD11b and CD62L adhesion molecules was determined with flow cytometry using respective monoclonal antibodies, while the neutrophil oxidative burst was evaluated with the Burst-test assay. Results: The current study results demonstrate that Adenocor does not affect the respiratory burst of polymorphonuclear leucocytes after Eschericha coli phagocytosis or PMA stimulation. The expression of adhesion molecules after intravenous adenosine at the dose of 140 µg/kg/min was not altered either. Conclusions: The analysis of the presented results provides unequivocal evidence to characterize the effects of adenosine on the selected parameters of immune reactions and the statistically insignificant increase of CD11b and CD62L was only moderate after a single intravenous dose of adenosine.